Hadith #3887 - Sahih al-Bukhari - Ibn al Musayyab (Sahih al-Bukhari)
Sa`d bin Abi Waqqas said, “Allah’s Messenger (ﷺ) mentioned both his father and mother for me on the day of the battle of Uhud.” He meant when the Prophet (ﷺ) said (to Sa`d) while the latter was fighting. “Let my father and mother be sacrificed for you!”
Grade: Sahih